Generating Subject-Oriented Process Models from Ad-Hoc Interactions of Cognitive Agents - Kannengiesser, Udo; Radmayr, Markus; Heininger, Richard; Meyer, Nils (2014 IEEE/WIC/ACM International Joint Conferences on Web Intelligence (WI) and Intelligent Agent Technologies (IAT), 2014)
To flexibly adapt business processes to changing requirements and new opportunities, it is often necessary to allow ad-hoc deviations from pre-defined process models. Agent systems can provide the autonomous behaviour needed for engaging in new interactions that were not included in the initial process model. However, the issue arises how these ad-hoc interactions can be captured for purposes of governance and process improvement. This paper presents an approach for generating subject-oriented process models from the cognitive models used by agents while interacting. It is based on the function-behaviour-structure (FBS) model of agents and its mapping onto key concepts of subject-oriented process modelling. We illustrate the approach using a mock-up implementation.